Performance evaluation of various diagnostics developed for a negative ion based neutral beam injector program in IPR. (1st July 2019) - Bandyopadhyay, M.; Deka, A.J.; Mukhopadhyay, D.; Singh, P.; Borah, D.; Pandey, A.; Tyagi, H.; Yadav, R.K.; Bhuyan, M.; Bharathi, P.; Chattopadhyay, A.K.; Pandya, K.; et al.
Abstract: The characteristics of a negative hydrogen ion (H-) source and its neutralization efficiency determine the performance of a negative ion based neutral beam injector (NNBI). Therefore, for the safe operation of an NNBI system, it is necessary to monitor the performance of the ion source and its beam through a systematic characterization process. A judicious selection of different diagnostics based on electrical, optical and thermal types and including calorimetric techniques are required. In this regard, a number of diagnostics are being developed under the NNBI R&D program in the Indian Test Facility (INTF). These diagnostics are versatile in nature in terms of their working principles and independent prototype experimental efforts have been carried out to establish them and prepare them for operational use. Electrical probes (EP), optical emission spectroscopy and cavity ring down spectroscopy (CRDS) are mainly envisaged for ion source plasma characterization. Additionally, standard electrical measurements in RF and DC power supply circuits are already in regular use in the operational experimental setups, ROBIN and HELEN-I, for monitoring the power supplies. Doppler shift spectroscopy (DSS) and optical emission tomography (TOMO) are developed for beam characterization in terms of divergence, stripping and beam profile. Some of these are characterized on separate prototype experiments and are already integrated and have been tested in the available operational plasma experimental setups: ROBIN and HELEN-I. The DSS system, with multiple lines of sight (LOS) (blue-shifted and red-shifted), is integrated in the ROBIN setup and CRDS is arranged in HELEN-I. The TOMO technique is used to find the beam power density profile from the hydrogen beam emitted Balmer line intensity. The optical brightness profile of a neutral beam due to beam emission radiation is proportional to the beam power density. In this regard, a tomography code based on maximum entropy is developed to reconstruct the 2D optical emissivity profile of the INTF beam by inverting the LOS integral of the brightness of the beam. The code has been validated with the simulated INTF beam power density profile, in terms of the mathematical functions representing it. In the present manuscript, the performance evaluations of these diagnostics are presented.